Perceived Job Performance and Constraints Hindering Performance of Krishi Vigyan Kendras in Mizoram - Lalhmachhuana, P.; Devarani , Loukham (Indian Journal of Extension Education, 2017)
The effectiveness of any organisation depends on the performance of the manpower engaged. This study was conducted in  three KVKs of Mizoram viz., Kolasib, Lunglei and Aizwal with the objective to assess the perceived job performance of  the scientific and technical staff of the KVKs and constraints faced by the staff which hinder their performance. Majority  (66.67%) of staff were found to be in medium job performance category. Performance was found to be most effective in  presenting and discussing field problems to farmers, conducting need based training programmes, attending official  meetings regularly and communicating solutions to farmers on field problems but found to be low in getting samples  tested (fertilizers /plant protection chemical /seed / soil & water), providing advisory through ICT and ensuring that rural  youths member within the KVK got a stable and reliable job. No special budgetary provision for conduct of demonstration  units, delay in releasing salary and lack of man power were the major constraints reported.
Keywords: KVK; Job Performance